Listened To Any Good Books Lately? The Prosodic Analysis of Audio Book Narration - Smiljana Komar (ELOPE, 2006)
The popularity of audio books is increasing. In the USA fewer people are reading books but many more are listening to them on tapes, CD’s and in MP3 format. The phenomenon is redefining the notion of reading. The purpose of the paper is to present some pros and cons of listening to books instead of reading them. The conclusions have been reached on the basis of a linguistic analysis of parts of two audio books belonging to two different literary genres: a crime novel (Dan Brown, The Da Vinci Code) and a comic one (Helen Fielding, Bridget Jones: The Edge of Reason).